The development of Emotional Quotient and learning behavior of Student Teachers Based on Learning Management with Active Learning Mixed Contemplative Education Approach - Wongkamjan, Jitraporn; saeng-ngam, Kanyawadee (Journal of Roi Et Rajabhat University, 2021)
The purposes of this research study was development of emotional quotient and learning behavior of Student Teachers Based on Learning Management with Active Learning Mixed Contemplative Education Approach. The sample group used in the study were 34 subjects who were studying in 1st year, of academic year 2019, of Mathematics Major Students in Faculty of Education Roi Et Rajabhat University, selected by purposive sampling. The instruments used in this study were 1) plans for learning activities based on Active Learning Mixed Contemplative Education approach, 2) assessment form for emotional quatient. 3) students journals 4) assessment form for learning behavior ,Mean and standard deviation were used for data analysis. The result was as follow :The emotional quotient of Student Teachers after learning Based on Learning Management with Active Learning Mixed Contemplative Education Approach was higher than before learning for all aspects, and In the analysis of learning behavior of students Student Teachers after learning Based on Learning Management with Active Learning Mixed Contemplative Education Approach for over all was at high level.